Chronic cranial window with access port for repeated cellular manipulations, drug application, and electrophysiology - Roome, Christopher J.; Kuhn, Bernd (Frontiers in Cellular Neuroscience, 2014)
Chronic cranial windows have been instrumental in advancing optical studies in vivo, permitting long-term, high-resolution imaging in various brain regions. However, once a window is attached it is difficult to regain access to the brain under the window for cellular manipulations. Here we describe a simple device that combines long term in vivo optical imaging with direct brain access via glass or quartz pipettes and metal, glass, or quartz electrodes for cellular manipulations like dye or drug injections and electrophysiological stimulations or recordings while keeping the craniotomy sterile. Our device comprises a regular cranial window glass coverslip with a drilled access hole later sealed with biocompatible silicone. This chronic cranial window with access port is cheap, easy to manufacture, can be mounted just as the regular chronic cranial window, and is self-sealing after retraction of the pipette or electrode. We demonstrate that multiple injections can be performed through the silicone port by repetitively bolus loading calcium sensitive dye into mouse barrel cortex and recording spontaneous cellular activity over a period of weeks. As an example to the extent of its utility for electrophysiological recording, we describe how simple removal of the silicone seal can permit patch pipette access for whole-cell patch clamp recordings in vivo. During these chronic experiments we do not observe any infections under the window or impairment of animal health.